Four Gharavasa-Dhamma, Sufficiency Economy Philosophy and Spiritual Well-Being of People at Ladphrao District in Bangkok - Phojad, Phrakhrusangkharak Kittichai; Wongkumsin, Theerapat (Mahachula Academic Journal, 2024)
The objectives of this research were to: (1) study the level of four Gharavasa-dhamma, sufficiency economy philosophy and spiritual well-being of people at Ladphrao district; (2) compare spiritual well-being of people at Ladphrao district by personal factors; (3) study the relationship between four Gharavasa-dhamma and spiritual well-being of people at Ladphrao district and (4) study the relationship between sufficiency economy philosophy and spiritual well-being of people at Ladphrao district. The sample were 400 people at Ladphrao district, in Bangkok. Data were collected by questionnaires. Data analysis used by a statistical package program. The statistical methods used by percentage, mean, standard deviation, t-test, F-test and Pearson’s product moment correlation coefficient. Results showed that: (1) four Gharavasa-dhamma, sufficiency economy philosophy and spiritual well-being of people at Ladphrao district were the relatively high level; (2) people at Ladphrao district had difference in occupation had difference spiritual well-being with statistically significant at .05 level; (3) four Gharavasa-dhamma positively related to spiritual well-being of people at Ladphrao district with statistically significance at .01 level and (4) sufficiency economy philosophy positively related to spiritual well-being of people at Ladphrao district with statistically significance at .01 level.